Stories From the Dendritic Cell Guardhouse - Hoober, J. Kenneth; Eggink, Laura L.; Cote, Robert (Frontiers in Immunology, 2019)
Abstract Professional phagocytic cells (dendritic cells [DCs], macrophages, monocytes, neutrophils and mast cells) utilize C-type (Ca2+-dependent) lectin-type (CLEC) receptors to identify and internalize pathogens or danger signals. As monitors of environmental imbalances, CLECs are particularly important in the function of DCs. When antigen presentation by DCs to the T cell receptor (TCR) is not coincident with expression of co-stimulatory factors such as CD40/80/86 by DCs and their interaction with CD40L and CD28 on T cells, and complemented by production of IL-12 and/or IFN-α/β, T cells become unresponsive. Thus the mode by which CLEC receptors on DCs are engaged can either elicit activation of T cells to achieve an immune response or induce T cell tolerance. This minireview illustrates these aspects with Dectin-1, DEC205, the mannose receptor and CLEC10A as examples.